2001
DOI: 10.1080/000164801300102897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cadmium on the Hearing System

Abstract: The functional resemblance between kidney proximal tubular and inner ear epithelial cells which has often been pointed out in the literature led us to hypothesize that nephrotoxic agents that cause renal tubular injury might also impair the function of inner ear cells. As one of the most toxic environmental nephrotoxic agents is cadmium, we aimed to study its effects on hearing experimentally in rats. In this study, increased blood and renal cortical cadmium levels were associated with high cadmium accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…Previous animal experiments show that solvents such as toluene, styrene, xylene, isopropyl alcohol, and ethyl benzene damage the cochlea (predominantly the supporting and outer hair cells) and provoke irreversible sensorineural hearing loss [12][16]. Furthermore, heavy metals such as cadmium, lead, mercury, and manganese induce the impairment (i.e., apoptosis and/or degeneration) of inner ear receptor cells, leading to auditory neuronal function disorders [23][27]. These findings provide a possible explanation that heavy metals and/or organic solvents condition the cochlea for damage triggered by oxidative stress produced by noise exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous animal experiments show that solvents such as toluene, styrene, xylene, isopropyl alcohol, and ethyl benzene damage the cochlea (predominantly the supporting and outer hair cells) and provoke irreversible sensorineural hearing loss [12][16]. Furthermore, heavy metals such as cadmium, lead, mercury, and manganese induce the impairment (i.e., apoptosis and/or degeneration) of inner ear receptor cells, leading to auditory neuronal function disorders [23][27]. These findings provide a possible explanation that heavy metals and/or organic solvents condition the cochlea for damage triggered by oxidative stress produced by noise exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several workplace studies suggest that such solvents are associated with an increased risk of hearing loss [17][22]. Heavy metals such as cadmium, lead, mercury, and manganese are reported to impair inner ear cells, leading to auditory function disorders in animal studies [23][27]. There is further evidence for their ototoxicity in human studies as well [28][30].…”
Section: Introductionmentioning
confidence: 99%
“…There is substantial evidence that implicates associations of impaired balance (Bhattacharya et al 1990, 1995, 2006, 2007; Chia et al 1994, 1996; Després et al 2005; Dick et al 1999; Iwata et al 2005; Kilburn and McKinley 1996; Linz et al 1992; Ratzon et al 2000; Viaene et al 2000; Yokoyama et al 1997, 2002), hearing loss (Agirdir et al 2002; Bertoni and Sprenkle 1988; Bleecker et al 2003; de Abreu and Suzuki 2002; Forst et al 1997; Hwang et al 2009; Lasky et al 2001; Ozcaglar et al 2001; Yokoyama et al 2002), and alterations in auditory evoked potential (Araki et al 1986; Bleecker et al 2003; Murata et al 1993) with exposure to lead and cadmium. However, it is not known whether exposure to lead and cadmium induces vestibular dysfunction specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have examined the effects of lead and cadmium exposures on neurobehavioral functions, such as declines in cognitive ability and visuomotor performance (Balbus-Kornfeld et al 1995; Viaene et al 2000), but there is increasing evidence suggesting that exposures are associated with hearing loss and alterations in auditory evoked potentials (Araki et al 1986; Forst et al 1997; Murata et al 1993; Ozcaglar et al 2001). In addition, several studies have reported that workers with occupational exposure to lead have significantly poorer postural balance responses than do unexposed workers (Chia et al 1994, 1996; Dick et al 1999; Iwata et al 2005; Linz et al 1992; Ratzon et al 2000; Yokoyama et al 1997, 2002).…”
mentioning
confidence: 99%
“…These observations emphasize the importance of studying the effects of Cd 2+ in other organs. Recently, Ozcaglar et al (2001) reported that hair cells are more sensitive to Cd 2+ than kidney tubule cells, and that the cochlear component of hearing is more vulnerable to Cd 2+ toxicity than other parts of the auditory system. However, the ototoxic mechanism of Cd 2+ on the auditory system is not completely understood.…”
mentioning
confidence: 99%